A Reading of Heidegger’s Reading of Immanuel Kant’s Critique Of Pure Reason - Ben Carlo Atim (Scientia, 2021)
This paper intends to argue over these subsequent ideas: first, that Heidegger’s employment of ‘retrieval’, ‘repetition’, or ‘thinking dialogue’ in his interpretation of Kant’s first Critique is, following Macann, quite hazardous and destructive but only on the surface. Heidegger's hermeneutical privilege to employ a specific interpretive frame in reading Kant seems to violate hermeneutics' fundamental maxim. This hermeneutic maxim is the inevitability of multiple interpretations. This can be seen in how Heidegger treated Kant's Critique of Pure Reason, where he announces that he “understand him (Kant) better than he (Kant) understood himself.” At first glance, his declaration exudes a kind of intellectual arrogance. However, I will show this is not so. Secondly, I will argue, based on the question of Heidegger’s appropriation of Kant’s ideas in his philosophical project, that he partly appropriated Kant but in a violent manner. As evident in his interpretation of the Critique of Pure Reason, Heidegger goes beyond Kant and forces the latter to speak through his text on the issues Heidegger thought to be in Kant. This raises the question of whether Heidegger properly situated and appropriated Kant in his text or not.